Stalkers: Specialists Versus Generalists - Sheridan, Lorraine (Journal of interpersonal violence, 2022)
It is known that many domestic violence (DV) offenders also commit violent and nonviolent offences that are not domestic in nature. Stalking frequently evolves from DV contexts. The present study used police data to explore (i) the extent to which stalking offenders in Western Australia specialize in stalking, (ii) the frequency of involvement in DV offending by stalking offenders, and (iii) the types of offences that co-occur with stalking offences. The dataset covered 404 individuals who were identified by the Western Australia Police Force as the offender for a stalking offence between January 1st, 2003 and July 30th, 2017. Only a minority of the offenders specialized in stalking, with the majority offending in other ways against the index victim and also offending against others via a broad range of offences. Although less than 10% were recorded as having carried out domestic assaults, more than half had broken restraining orders. Like DV offenders, the stalkers in this sample were largely generalist offenders. It was not clear, however, what proportion of offences against the same index victim were directly related to stalking. Stalking is a course of conduct that often involves individual acts that may be offences in themselves. What is clearer is the finding that for many stalkers, stalking forms part of a wider pattern of antisocial activity. Those stalkers who do not specialize in stalking may be less likely to benefit from intervention efforts that are focused solely on stalking.